Screening Gene Mutations in Chinese Patients With Benign Essential Blepharospasm - Dong, Hongjuan; Luo, Ying; Fan, Shanghua; Yin, Bo; Weng, Chao; Peng, Bin (Frontiers in Neurology, 2020)
Objective: This study aimed to screen gene mutations in Chinese patients with benign essential blepharospasm (BEB) to understand the etiology of BEB. Methods: Twenty BEB patients diagnosed by clinical manifestations between April 2015 and October 2015 were enrolled. All the cases were investigated by questionnaires about general conditions, social behavioral factors, environmental factors, psychological factors, genetic factors, previous diseases. In each patient, total 151 genes related to movement disorders were analyzed by second-generation sequencing. Results: Two patients had a family history of BEB, and they had SYNE1 and CIZ1 mutation, respectively. We found SYNE1 mutation in seven patients, CIZ1 mutation in two patients, CACNA1A mutation in two patients, LRRK2 mutation in two patients, FUS mutation in two patients. C10orf2, TPP1, SLC1A3, PNKD, EIF4G1, SETX, PRRT2, SPTBN2, TTBK2 mutations were found in only one patient, respectively, while no any mutations in the 151 genes were found in two patients. Some patients had mutations in two genes. Conclusion: Similar to other dystonia diseases, genetic factors, especially SYNE1 and CIZ1 mutations, contribute to the etiology of BEB.